STRATEGI STP DAN 4P PADA MARKETING PRODUK LAYANAN RAWAT JALAN DI RUMAH SAKIT SULTAN IMANUDDIN PANGKALAN BUN DI ERA PANDEMI COVID-19 - Sari, Noormaya (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2022)
The COVID-19 pandemic has had a wide impact on the marketing of hospital product and services. The purpose of this study is to analyze about outpatient services at Sultan Imanuddin Pangkalan Bun Hospital (RSSI) and determine what marketing strategies are suitable in marketing hospital service products during the COVID-19 pandemic. Methods : This study is a mixed method, descriptive research which combined with a qualitative approach. Results : based on the STP strategy, RSSI used demographic, geographic, biographic and behavioral segmentation. Targeting is done based on area and insurance membership. RSSI is positioned as General Hospital, despite handling Covid patients, non Covid services are still maintained. Based on the 4 P concepts (product, price, place and promotion) that had been carried out is quite good. Conclusions : The STP and 4 P strategies at RSSI is good enough. However, further socialization is needed to the public regarding the separation of locations for Covid and non Covid services, as well as the implementation of well executed health protocols, in the hope of that it can reduce people’s fears of coming for treatment.